Self-Efficacy Related to Work and Transformative Leadership of School Principals as Explanatory Factors for Dispositional Resistance to Change - Loi Zedda, Maude; Thibodeau, Stéphane; Frenette, Eric; Forget, Pascal (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2025)
This study addresses the lack of knowledge about the relationship between school principals’ self-efficacy related to work, transformative leadership, and disposition to resist change. One hundred and twenty-six respondents completed three measurement scales: the Scale of School Principals’ Self-Efficacy, the Self-Reported Leadership Scale, and the Resistance to Change Scale. The results indicate that there are links between different dimensions of school principals’ self-efficacy related to work and dispositional resistance to change and that certain dimensions of transformative leadership play an intermediate role in these relationships. These results are discussed in the light of theories and studies relating to the three concepts.